Rockfall from an increasingly unstable mountain slope driven by climate warming - Stoffel, Markus; Trappmann, Daniel; Coullie, Mattias Ian; Ballesteros Canovas, Juan Antonio; Corona, Christophe (Nature Geoscience, 2024)
Rockfall in high-mountain regions is thought to be changing due to accelerating climate warming and permafrost degradation, possibly resulting in enhanced activity and larger volumes involved in individual falls. Yet the systematic lack of long-term observations of rockfall largely hampers an in-depth assessment of how activity may have been altered by a warming climate. Here we compile a continuous time series from 1920 to 2020 of periglacial rockfall activity using growth-ring records from 375 trees damaged by past rockfall at Täschgufer (Swiss Alps). We show that the ongoing warming favours the release of rockfall and that changes in activity correlate significantly with summer air temperatures at interannual and decadal timescales. An initial increase in rockfall occurred in the late 1940s to early 1950s following early twentieth century warming. From the mid-1980s, activity reached new and hitherto unprecedented levels. This long-term record of rockfall activity can help to inform the design of vital mitigation and risk reduction measures in inhabited mountain environments.